Earthquake Early Warning through Abnormal Animal Behaviour - Vasudeva, S. P. (Indian Forester, 2017)
Earthquake is one of the most destructive natural hazards causing destruction. However, there is no early warning and forecasting system in place unlike cyclones, floods and tsunami. It is usually predicted seconds before it strikes through instruments installed for this purpose when managing the destruction is not possible. Animals behaving strangely which is not usually normal before an earthquake have been reported. There is need to standardise this abnormal animal behaviour in such a way that it always gives uniform results and if need be in linking with instruments so as to consider it as a reliable and sure early warning before the earthquake strikes. This is urgently required so as to reduce risks that cause loss of lives and properties.